Solution processed F doped ZnO (ZnO:F) for thin film transistors and improved stability through co-doping with alkali metals1. Issue 8 (28th February 2015) - Chang, Jingjing; Lin, Zhenhua; Lin, Ming; Zhu, Chunxiang; Zhang, Jie; Wu, Jishan
<x xml:space="preserve">Abstract</x> FETs based on ZnO doped with F and alkali metals showed largely improved charge carrier mobility, shelf-life stability and bias stress stability.